Mediator subunit 12 is required for neutrophil development in zebrafish. - Maria-Cristina Keightley; Judith E Layton; John W Hayman; Joan K Heath; Graham J Lieschke (PLoS ONE)
Hematopoiesis requires the spatiotemporal organization of regulatory factors to successfully orchestrate diverse lineage specificity from stem and progenitor cells. Med12 is a regulatory component of the large Mediator complex that enables contact between the general RNA polymerase II transcriptional machinery and enhancer bound regulatory factors. We have identified a new zebrafish med12 allele, syr, with a single missense mutation causing a valine to aspartic acid change at position 1046. Syr shows defects in hematopoiesis, which predominantly affect the myeloid lineage. Syr has identified a hematopoietic cell-specific requirement for Med12, suggesting a new role for this transcriptional regulator.